Clinical dose-response relationship of fluticasone propionate in adults with asthma. Issue 1 (23rd December 2003) - Masoli, M; Weatherall, M; Holt, S; Beasley, R
Abstract : Background: A study was undertaken to examine the dose-response relation of inhaled fluticasone in adolescents and adults with asthma. Methods: A meta-analysis was carried out of randomised clinical trials that presented data on at least one outcome measure of asthma and that used at least two doses of fluticasone given twice daily. The main outcome measures were forced expiratory volume in 1 second (FEV1 ), morning peak expiratory flow (amPEF), β agonist use, and withdrawals due to exacerbations of asthma. Results: Seven studies of 2431 adolescents and adults with moderate to severe asthma met the inclusion criteria for the meta-analysis. Four studies examined a dose of >500 µg/day. For all outcome measures there were no statistically significant differences between a dose of 200 v 500 μg/day, 500 v 1000 μg/day, and 200 v ⩾500 µg/day, although the point estimates favoured the higher doses. The mean improvement for FEV1 and amPEF resulting from an increase in dose from 200 to ⩾500 µg/day was 0.07 l (95% CI −0.01 to 0.14) and 5.9 l/min (95% CI −3.0 to 15.3), respectively. The odds ratio for withdrawals with 200 µg/day compared with ⩾500 µg/day was 1.27 (95% CI 0.78 to 2.07). Conclusions: In adolescents and adults with asthma, most of the therapeutic benefit of fluticasone is achieved with a total daily dose of 200 µg/day with minimal further clinical benefit achieved with higher doses. This conclusion is qualified by the recognition that there is considerable individual variability in the response to inhaled corticosteroids in asthma, which would suggest that some patients may obtain a greater clinical benefit at higher doses.